(untitled) (Research, Society and Development, 2021)
Virtual Population Analysis (VPA) is a diagnostic tool that providing valuable input for management decisions to sustainable catches for marine fisheries. Industrial shrimp trawling produces one of the most valuable export commodities in the Brazilian fishery sector. Due to the profitability, there is pressure on government agencies to increase the number of fishing licenses. The present study used the body-length data available for the industrial southern brown shrimp trawling fleet of the Amazon Continental Shelf (ACS), Brazil, to estimate the current maximum sustainable yield and test the potential effects of increased effort on the sustainability of this fishery. The available data encompasses 13 years of onboard monitoring of shrimp trawling. The VPA was run in an Excel spreadsheet. The results indicate that the ACS shrimp stock has high fishing (F) mortality rates, although exploitation levels can be considered adequate below the MSY. An increase of up to 40% in fishery effort – including the expansion of the number of vessels – would not result in overfishing, although we would not recommend an increase in effort, as this may increase impacts on the bycatch fauna and eventual economic losses in the event of the failure of recruitment.